Breaking the Nd3+-sensitized upconversion nanoparticles myth about the need of onion-layered structures. Issue 26 (21st June 2018) - Estebanez, Nestor; Ferrera-González, Juan; Francés-Soriano, Laura; Arenal, Raul; González-Béjar, María; Pérez-Prieto, Julia
Abstract : Excitation at 800 nm effectively triggers the upconversion emission of NaYF4 :Yb, Er(Tm)/NaYF4 core–shell nanoparticles with Nd 3+ anchored at the organic capping by using cucurbituril[7] as an adhesive. Abstract : Up to now, most strategies to build efficient 800 nm-light responsive upconversion nanoparticles (UCNPs) have included onion-layered structures, in which Nd 3+ is confined within the inorganic crystal structure of at least one layer. We report here an easy room-temperature modular preparation of core–shell UCNPs consisting of NaYF4 :Yb, Er(Tm)/NaYF4 (UCCS ) with Nd 3+ anchored at the organic capping by using cucurbituril[7] (CB[7]) as an adhesive. Strikingly, excitation at 800 nm effectively triggers the upconversion emission of UCCS @CB[7]@Nd nanohybrids.